2018
DOI: 10.3390/w10081039
|View full text |Cite
|
Sign up to set email alerts
|

Tree Water Dynamics in a Semi-Arid, Pinus brutia Forest

Abstract: This study aims to examine interactions between tree characteristics, sap flow, and environmental variables in an open Pinus brutia (Ten.) forest with shallow soil. We examined radial and azimuthal variations of sap flux density (Jp), and also investigated the occurrence of hydraulic redistribution mechanisms, quantified nocturnal tree transpiration, and analyzed the total water use of P. brutia trees during a three-year period. Sap flow and soil moisture sensors were installed onto and around eight trees, sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 70 publications
(81 reference statements)
1
20
0
Order By: Relevance
“…For the cpSSR data, HAPLOTYPE v.1.05 [ 51 ] was used to estimate the number of alleles at chloroplast SSR loci (N acpSSR ), number of haplotypes detected in each population (N b ), effective number of haplotypes (N e ), genetic diversity (Dv), haplotype richness (H r ) and the number of private haplotypes (Prv). A parsimony network illustrating genetic relationships between haplotypes was inferred using the software PopArt [ 52 ], assuming single-step mutations between alleles.…”
Section: Methodsmentioning
confidence: 99%
“…For the cpSSR data, HAPLOTYPE v.1.05 [ 51 ] was used to estimate the number of alleles at chloroplast SSR loci (N acpSSR ), number of haplotypes detected in each population (N b ), effective number of haplotypes (N e ), genetic diversity (Dv), haplotype richness (H r ) and the number of private haplotypes (Prv). A parsimony network illustrating genetic relationships between haplotypes was inferred using the software PopArt [ 52 ], assuming single-step mutations between alleles.…”
Section: Methodsmentioning
confidence: 99%
“…Suit of approaches was used to test whether there were differences in the circulating genotypes in complicated and uncomplicated malaria cases by exploring how microsatellite haplotypes clustered. We used the Haplotype Analysis software v1.04 [ 37 ] on all the multi-locus genotypes that we could unambiguously identify. Thus, a limitation in these analyses is that complex infections with differences at more than two loci were not included because the haploid genotypes could not be inferred.…”
Section: Methodsmentioning
confidence: 99%
“…The vapor pressure deficit, determined by air temperature and relative humidity, may be responsible for the variation in sap flow on low temperature large percentage cloud cover days. Eliades et al [26] found that during negative temperatures, reverse sap flow was occurring. This may be one of the explanations of the poor correlation of the TWD with sap flow.…”
Section: Discussionmentioning
confidence: 99%
“…Sap flow sensors (type SF-G, Ecomatik, Munich, Germany) were installed at a stem height of 1.5 m facing north with flexible foamed plastic wrapping on the outside to protect them from rainfall and solar radiation interference. Although the potential azimuthal and radial variations of sap flux density should not be ignored [26], we only selected the north side for device setting, which is the usual practice when there is a limitation in the number of the sensors. Three sets of device sensors were installed on trees where diameter variation sensors were deployed.…”
Section: Data Measurement Of Stem Diameter Variations Sap Flow and mentioning
confidence: 99%